On the Medieval Theory of Signs. - Eco, Umberto (John Benjamins Pub. Co., 1989)
In the course of the long debate on the nature and the classification of signs, from Boethius to Ockham, there are at least three lines of thought: the Stoic heritage, that influences Augustine, Abelard, Francis Bacon; the Aristotelian tradition, stemming from the commentaries on De Interpretatione; the discussion of the grammarians, from Priscian to the Modistae. Modern interpreters are frequently misled by the fact that the various authors regularly used the same terms. Such a homogeneous terminology, however, covers profound theoretical differences. The aim of these essays is to show that t.